More hip complications after total hip arthroplasty than after hemiarthroplasty as hip fracture treatment: analysis of 5, 815 matched pairs in the Swedish Hip Arthroplasty Register. (3rd March 2020) - Hansson, Susanne; Bülow, Erik; Garland, Anne; Kärrholm, Johan; Rogmark, Cecilia
Abstract : Background and purpose — Total hip arthroplasty (THA) is increasing as treatment of displaced femoral neck fractures. Several studies compare hemiarthroplasty (HA) with THA, but results vary and few studies report on medical complications. We examined the outcome of THA and HA with a focus on medical complications, hip complications, and death. Patients and methods — Data from the Swedish Hip Arthroplasty Register on 30, 953 acute hip fracture patients treated with cemented THA or HA in 2005–2011 were cross-matched with Statistics Sweden for socioeconomic data and with the National Patient Register for diagnostic codes representing medical complications within 180 days or hip complications within the study period. Propensity score matching was used to create comparable groups based on age, sex, income, level of education, marital status, Elixhauser index, and year of surgery. Logistic regression models were created for each outcome. Results — 81% were treated with HA, 73% and 71% were female (HA and THA respectively). Matching resulted in 2 groups of 5, 815 patients each. THA was associated with fewer medical complications (OR = 0.83; 95% CI 0.76–0.91) and lower 1-year mortality (OR = 0.42; CI 0.38–0.48), but more hip complications (OR = 1.31; CI 1.20–1.43). Interpretation — THA as treatment of hip fracture was associated with more hip-related complications than HA. The results on mortality and medical complications are, rather, influenced by residual confounding than by the implant design per se. An expansive use of THAs for hip fracture treatment, at the expense of HAs, is not recommended based on our findings if hip complications are to be avoided.